Imminent accession of Artificial Intelligence based Forensic Exploratory with Data Mining Analysis - Umar, S; Praveen, A; Gouse, S; Deepthi, N (International Journal of Computer Sciences and Engineering, 2025)
Data mining is part of the interdisciplinary field of knowledge discovery in databases. Data Mining research began in 1980 and has grown rapidly in 1990s.Specific methods developed in disciplines such as artificial intelligence, machine learning and pattern recognition used in data mining. Data mining has been introduced in various sectors. key functional area of mining technology of the World Wide Web Recently mining techniques applied to the data in the field of criminal law, but that digital forensics. Examples can be found misleading to establish criminal identity criminal groups involved in illegal activities and much more. the politics of data mining technology typically generate a summary of large amounts of data. Digital Forensics is the area of research discoveries and advanced tip. Canvass search field, and digital forensic applications are developing rapidly with the economic giant digital information. law enforcement and military agencies have confidence in digital forensics today. Since the age of information is the speed of thought and data stored in digital form, the need for an accurate intellectual interception, and timely decision errors close to zero digital data processing cores issue. This article will research focusing on the role of data mining techniques for digital forensics. also identifies how data-mining techniques can be applied in the field, a digital forensic forensic examiner to take the next step in the process, which is cost-effective digital program is a crime.